The Armenian Translated Tale in the International Context - Jivanyan, Alvard (Bulletin of Yerevan University B: Philology, 2022)
The present article deals with direct and mediated translations of Armenian fairy tales presented in chronological order. Our research includes a number of major collections of Armenian tales told in non-Armenian milieux and recorded in languages other than Armenian. The collectors of these tales have apparently functioned both as recorders and translators. It is to be noted that there exist no printed versions of the mentioned tales in Armenian. The study and systematization of translated tale collections are important for making the Armenian fairy-tale material more distinct and identifiable for folklore and fairy-tale scholars.